2017
DOI: 10.1159/000480091
|View full text |Cite
|
Sign up to set email alerts
|

Quantification of Bisoprolol and Metoprolol in Simultaneous Human Serum and Cerebrospinal Fluid Samples

Abstract: Background: Bisoprolol and metoprolol are moderately lipophilic, beta(1)-selective betablockers reported to cause adverse effects in the central nervous system (CNS), such as sleep disturbance, suggesting that both drugs may reach relevant concentrations in the brain. CNS beta(2)-receptor blockade has been suspected to be related to such effects. The higher molecular size of bisoprolol (325 Dalton) and the higher beta(1)-selectivity compared to metoprolol (267 Dalton) would suggest a lower rate of CNS effects.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
6
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 17 publications
1
6
0
Order By: Relevance
“…In the present study, patients receiving carvedilol (40%) and/or bisoprolol (56%) accounted for over 95% of patients receiving β-blockers. There are few reports of the associations between these newer β-blockers and delirium (Aikoye et al, 2019;Shigaroudi et al, 2018). The result of the present study may support the above guidelines and the hypothesis that β-blockers may be useful adjuncts for managing delirium.…”
Section: Discussionsupporting
confidence: 85%
See 1 more Smart Citation
“…In the present study, patients receiving carvedilol (40%) and/or bisoprolol (56%) accounted for over 95% of patients receiving β-blockers. There are few reports of the associations between these newer β-blockers and delirium (Aikoye et al, 2019;Shigaroudi et al, 2018). The result of the present study may support the above guidelines and the hypothesis that β-blockers may be useful adjuncts for managing delirium.…”
Section: Discussionsupporting
confidence: 85%
“…It is known that β-blockers, especially the very lipophilic agents such as propranolol, are associated with the development of delirium (Alagiakrishnan & Wiens, 2004). However, although lipophilicity is considered to be one of the factors that affect the central nervous system (CNS), other drug-specific factors may affect the CNS (Shigaroudi et al, 2018). For example, penetration of the CNS by atenolol is limited because of its hydrophilic nature; therefore, its untoward effects on the CNS should be fewer compared with other β-blockers, but it has been reported that atenolol at high doses may cause organic brain syndrome (Arber, 1988).…”
Section: Discussionmentioning
confidence: 99%
“…Bisoprolol (zebeta ® ; BIS), a phenoxy-2-propanol derivative, is recognized as an oral synthetic selective blocker of β 1 -adrenoceptor with antioxidant activity which exerts a number of potentially beneficial pharmacological effects such as atrial fibrillation, heart failure and postural tachycardia syndrome [1,2,3,4]. Due to its lipophilic nature, it facilitates entry into brain tissue to produce regulatory actions on central neurons [5,6]. Previous reports have demonstrated that BIS could bind to β 1 -adrenergic receptors inherently existing in brain areas including the pituitary gland and hippocampus [7,8,9,10,11].…”
Section: Introductionmentioning
confidence: 99%
“…Data are presented as median and interquartile range patients who took bisoprolol. Bisoprolol is a moderately lipophilic drug that penetrates the brain, and its concentrations in the cerebrospinal fluid are comparable to those in plasma [5]. In contrast to other beta-blockers such as carvedilol or labetalol, it may also influence the production of melatonin which is a key regulator hormone of human sleep and circadian rhythm [18][19][20].…”
Section: Discussionmentioning
confidence: 99%
“…In particular, sleep-related side effects include drowsiness, sleepiness, fatigue, nightmares and other parasomnias [3,4]. Lipophilic drugs such as propranolol, metoprolol or betaxolol can enter CNS and achieve high concentration in the cerebrospinal fluid, while moderately lipophilic beta-blockers such as bisoprolol, nebivolol or carvedilol only partly penetrate through the blood-brain barrier [5]. In contrast, hydrophilic drugs such as sotalol or atenolol have a weak passage with poor distribution in CNS [6].…”
Section: Introductionmentioning
confidence: 99%